The book of chess - Jacobus, de Cessolis, active 1288-1322 (Italica Press, 2008)
"An English translation of the most popular medieval book on chess, which uses the history of the games, its players and their moves as the basis for a discourse on life comprised of tales and anecdotes from a wide variety of ancient and medieval literary sources"--Provided by publisher